2011
DOI: 10.1039/c1cy00261a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of distortion of PO4 tetrahedron on the photocatalytic performances of BiPO4

Abstract: Three kinds of crystal phase BiPO 4 (HBIP, nMBIP and mMBIP) were selectively synthesized by a hydrothermal method. The governed factors for the formation of three crystal phase of BiPO 4 were both on the acidity of the solution and reaction temperature. The BiPO 4 with nMBIP phase structure showed higher activity for degradation of MB solution under UV irradiation than HBIP and mMBIP. The catalytic activity per surface area activity of nMBIP (3.8Â10 5 h À1 m À2 ) was about ten times higher than that of P25(1.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(86 citation statements)
references
References 37 publications
5
81
0
Order By: Relevance
“…5 shows the UV-vis diffuse reflectance spectra (UV-DRS) of BiPO 4 and Er 3+ :YAlO 3 /BiPO 4 -7 powders. The absorption edge of BiPO 4 is 285 nm, which is consistent with previous reports [11,19]. In addition, the absorption edge of Er 3+ :YAlO 3 /BiPO 4 -7 shifted to 282 nm.…”
Section: Photocatalytic Evaluationssupporting
confidence: 90%
See 1 more Smart Citation
“…5 shows the UV-vis diffuse reflectance spectra (UV-DRS) of BiPO 4 and Er 3+ :YAlO 3 /BiPO 4 -7 powders. The absorption edge of BiPO 4 is 285 nm, which is consistent with previous reports [11,19]. In addition, the absorption edge of Er 3+ :YAlO 3 /BiPO 4 -7 shifted to 282 nm.…”
Section: Photocatalytic Evaluationssupporting
confidence: 90%
“…Heterogeneous photocatalysts offer a possible solution on decomposing organic pollutants in a sustainable way [6][7][8][9]. Bismuth phosphate, as a novel nonmetal oxy-acid salt photocatalyst, has firstly been reported by Pan et al [10][11][12]. The photocatalytic degradation of MB over BiPO 4 is twice as efficiency as over P25 TiO 2 in spite of the fact that the absorbance edge of BiPO 4 is about 322 nm, which deduced from its conduction and valence band position at À0.63 and 3.2 eV, respectively.…”
mentioning
confidence: 99%
“…The BiPO 4 was ascribed to indirect transition, so the n value was given as 4 [43]. From the plots of ðahnÞ 1=2 versus ðhnÞ in Fig.…”
Section: Mechanism Of Enhanced Photocatalytic Activitymentioning
confidence: 99%
“…Meanwhile, size-controlled synthesis of BiPO 4 nanocrystals with the small size could further enhanced photocatalytic performance, for the high specific surface area and short mobility distance for carriers to the surface are recognized as the key factors for the high photocatalytic activity of nanocrystals [6]. Further research indicated that high-concentration oxygen vacancies introduced on the BiPO 4 nanorods could extend the photo-response wavelength range and improve the photocatalytic activity [7], meanwhile, the inductive effect of PO 4 3-helps the e -/h + separation, which plays an important role in its excellent photocatalytic activity [8]. Nevertheless, the BiPO 4 photocatalyst suffers from two main problems, the high recombination of photo-induced electron-holes pairs and the low solar energy conversion efficiency, which significantly restricted its practical applications [9].…”
Section: Introductionmentioning
confidence: 97%